Apokaliptiek en Openbaring: 'n Kritiese evaluering van Malina en Pilch se “Social-Science commentary on the Book of Revelation” (Afrikaans) - Geyser, Piet A. (University of Pretoria, 2013)
Dissertation (MA (Biblical Studies))--University of Pretoria, 2007.